Pediatric age-adjusted shock index as a tool for predicting outcomes in children with or without traumatic brain injury. Issue 5 (November 2021) - Reppucci, Marina L.; Phillips, Ryan; Meier, Maxene; Acker, Shannon N.; Stevens, Jenny; Moulton, Steven L.; Bensard, Denis
Abstract : BACKGROUND: The pediatric age-adjusted shock index (SIPA) accurately identifies severely injured children following trauma without accounting for neurological status. Understanding how the presence of traumatic brain injury (TBI) affects the generalizability of SIPA as a bedside triage tool is important given high rates of TBI in the pediatric trauma population. We hypothesized that SIPA combined with TBI (SIPAB+) would more accurately identify severely injured children. METHODS: Patients (1–18 years old) in the American College of Surgeons Pediatric Trauma Quality Improvement Program database (2014–2017) with an elevated SIPA upon arrival to a pediatric trauma center were included. Pediatric age-adjusted shock index combined with TBI was defined as elevated SIPA with Glasgow Coma Scale score of ≤8. Pediatric age-adjusted shock index without TBI (SIPAB−) was defined as elevated SIPA with Glasgow Coma Scale score of >9. Patients were stratified into SIPAB+ and SIPAB−. A subanalysis of patients with isolated brain injury and those with brain injury and multisystem injuries was also performed. Data were compared through univariate models and three separate logistic regression models. RESULTS: Overall, 25, 068 had an elevated SIPA, with 12.3% classified as SIPAB+ and the remainder SIPAB−. Patients classified as SIPAB+ received more blood transfusions within 4 hours of injury and had higher mortality rates. On logistic regression, SIPAB+ patients had significantly higher odds of early blood transfusion and a combination of both. Mortality and early blood transfusion were also higher in SIPAB+ patients on subanalysis for patients with isolated TBI and those with multisystem injuries. CONCLUSION: The use of SIPAB+ as a bedside triage tool accurately identifies traumatically injured children at high risk for early blood transfusion and/or death while incorporating the presence of neurological injury. This is true for patients with isolated TBI and those with multisystem injury, indicating its utility in predicting outcomes for TBI patients with elevated SIPA regardless of presence of concomitant injuries. Incorporation of this as a triage tool should be considered to better predict resources in this population. LEVEL OF EVIDENCE: Prognostic, level III.